The biology and rate of reproduction and the morphology of the immature stages of Apanteles angaleti Muesebeck (Hymenoptera: Braconidae). - Narayanan, E. S.; Subba Rao, B. R.; Gangrade, Govind Amarchand (Contributions to Entomology = Beiträge zur Entomologie, 1956)
1. Apanteles angaleti Muesebeck has been recently found to parasitise the larvae of Platyedra gossypiella (Saunders), a serious pest of cotton in India and other cotton growing regions of the world. - 2. The parasite was mass bred in the parasite laboratory of the Indian Agricultural Research Institute on an alternate host, Coreyra cephalonica Stainton. - 3. The life history of the parasite, including the incubation period of the egg, duration of different larval stages and the mode of emergence from the host body has been studied. The life history under controlled conditions from egg to adult occupied 29 to 44 days. - 4. The rate of reproduction, the longevity and fecundity have been studied. - 5. The effect of parasitisation on the host results in the retardation of growth, irregular and less number of moults and also loss of weight. - 6. The morphology of the immature stages has been described. A. angaleti has 3 instars of which the 3rd instar lasts only for a few hours. - 7. The anatomy of the caudal vesicle of the second instar has been studied. The functions of the caudal vesicle have been investigated and discussed. It is established that the caudal vesicle is more of a respiratory function. - 8. The mouth parts, chaetotaxy and the morphology of the third instar larva has been studied.